Development and improvement of HR policy in the transport industry - Karanina Elena; Kotandzhyan Asya; Vershinina Natalya; Davydova Julia (E3S Web of Conferences, 2020)
The article discusses various approaches to the formation of personnel policy in the transport industry, provides an overview of research and work on this topic; substantiates the need for the implementation of certain measures for the development and improvement of human resource management; the interrelation between the management of the personnel component and the improvement of the quality management system is reflected. Speaking about the importance of improving personnel policy in the transport industry, it is emphasized the need to include mandatory activities as part of an innovative approach to human capital management.